On the Issue of Determining the Authorship of an Intellectual Product, Created with the Help of Artificial Intelligence - Lushchyk, Ihor (Problems of legality, 2025)
The relevance of the research topic is due to the rapid growth in the number and quality of works created using artificial intelligence technologies and disputes among legal professionals regarding the determination of authorship of such works. The purpose of the article is to study the problems with determining copyright in AI-generated content and to analyse the legislation and case law on these issues. The study applies formal and logical methods, generalisation, analysis and synthesis, systemic and structural, and comparative legal methods of scientific knowledge. The author examines the issues of adaptation of the legislative framework in the field of intellectual property to modern challenges in connection with the dissemination of content created using advanced computer technologies. The mechanisms and regularities of creation of works containing computer-generated content are considered. The article analyses Ukrainian legislation and international judicial practice on determining copyright in works created by artificial intelligence. Based on the study, the author concludes that a work created by artificial intelligence can be recognised as an author even with minimal human involvement, and provides recommendations for the settlement of copyright issues related to the use of computer technology products.